ANALYSIS OF PTUN MEDAN NUMBER 165/G/2023/PTUN. MDN ON BLACKLISTING SANCTIONS IN THE PERSPECTIVE OF SIYASAH QADHAIYYAH: ANALISIS PTUN MEDAN NOMOR 165/G/2023/PTUN.MDN TENTANG SANKSI DAFTAR HITAM DALAM PERSPEKTIF SIYASAH QADHAIYYAH - Siti Afsah; Annisa Sativa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study is motivated by a legal controversy surrounding the imposition of a blacklisting sanction against PT. Bumi Aceh Citra Persada through the Administrative Court (PTUN) Medan Decision No. 165/G/2023/PTUN.MDN. The main problem addressed in this research is the judicial reasoning underlying the ruling and the extent to which the decision reflects the principle of substantive justice from the perspective of siyasah qadhaiyyah (Islamic judicial politics). The purpose of this study is to analyze the judges’ legal considerations and evaluate their conformity with Islamic legal principles, particularly within the framework of siyasah qadhaiyyah. This research employs a library-based qualitative method with a normative juridical approach, utilizing primary sources such as the PTUN decision, and secondary sources including books, journals, articles, and relevant legal regulations. Data were collected through literature review and analyzed using a qualitative content analysis method. The findings indicate that the judges’ considerations were primarily based on Government Regulation No. 12 of 2021 concerning Government Procurement of Goods and Services, which outlines the mechanism for blacklisting sanctions against service providers who violate provisions. However, from the perspective of siyasah qadhaiyyah, issues of proportionality and substantive justice remain, as the sanction does not fully consider the aspects of public welfare (maslahah) and the protection of the parties’ rights. Therefore, this study concludes that harmonization between positive law and Islamic principles of justice is essential in the application of administrative sanctions.